Precise identification of cascading alpha satellite higher order repeats (HORs) in T2T-CHM13 assembly of human chromosome 3 - Glunčić, Matko; Vlahović, Ines; Rosandić, Marija; Paar, Vladimir (Croatian medical journal, 2024)
To precisely identify and analyze alpha-satellite higher-order repeats (HORs) in T2T-CHM13 assembly of human chromosome 3. From the recently sequenced complete T2T-CHM13 assembly of human chromosome 3, the precise alpha satellite HOR structure was computed by using the novel high-precision GRM2023 algorithm with global repeat map (GRM) and monomer distance (MD) diagrams. The major alpha satellite HOR array in chromosome 3 revealed a novel cascading HOR, housing 17mer HOR copies with subfragments of periods 15 and 2. Within each row in the cascading HOR, the monomers were of different types, but different rows within the same cascading 17mer HOR contained more than one monomer of the same type. Each canonical 17mer HOR copy comprised 17 monomers belonging to 16 different monomer types. Another pronounced 10mer HOR array was of the regular Willard's type. Our findings emphasize the complexity within the chromosome 3 centromere as well as deviations from expected highly regular patterns.